The atheist's creed - Palmer, Michael, 1945- (Lutterworth Press, 2010)
In The Atheist's Creed a prominent and widely-read contemporary philosopher, Dr Michael Palmer, presents the most comprehensive anthology of the major philosophical arguments for atheism now before the public. While the so-called 'new atheism' of RichardDawkins and others has attracted considerable publicity, it is these philosophical arguments that have down the ages provided the principal landmarks in the unfolding and increasingly widespread belief that no God exists. Using a combination of extracts,detailed introductions, biographies and extensive bibliographies, the author guides the reader through the history of atheism, from the time of the early Greeks down to the present day. In this analysis particular attention is given to the writings of Hume, Nietzsche, Marx and Freud. The Atheist's Creed requires no specialist knowledge of philosophy. Each chapter is structured around a single theme and the various authors coordinated to allow the full force of the particular atheistic argument to emerge.The result is a compelling and powerful assessment of the case for atheism, which will be essential and fascinating reading for student and non-student alike and for all those concerned with the fundamental question: whether or not there is a God.